Change in plasma concentrations of lipid peroxidation products in patients with acute viral hepatitis - , Ali Rıza ERBAY, Ayşe ERBAY, Nurcan BAYKAM, Şebnem EREN, Başak Dokuzoğuz (Turkish Journal of Gastroenterology 1, 2019)
-